A New Regime of Governing Childhood? Finland as an Example - Timo Harrikari; Mirja Satka (Social Work and Society, 2006)
Children's problems have become familiar to the Finnish public since the media has portrayed many children as being 'at risk of exclusion' or involved in delinquent acts. The new public concern for children and childhood has been followed by interests in regulating and intervening in the lives of children and their families also in many other countries (e.g. Bloch et al 2003, Parton 2006). The simultaneous emergence of new models of welfare states and social-economic policy regime reforms present childhood (and parenting) as the current target of 'social investments' (Esping-Andersen 2002; Lister 2003). We assume the resulting improved investment, moral panic and social control are aimed at firmly linking childhood to the social economic goals of success in the markets of global capitalism, although we do not presently have a comprehensive picture of what is going on with regard to Finnish socio-legal practices. Hence we have started a research project which aims to critically analyse the inexplicable transformation in child welfare work in Finland both from an historical and a sociological viewpoint in the frame of generational and social legitimacy and solidarity. The study aims to develop a history of the present in the field of Finnish child welfare and to some extent also in comparison with some other European countries (see http://www.valt.helsinki.fi/blogs/sociolegal ).